ESTIMATION OF SOIL NITROGEN, PHOSPHOROUS AND POTASSIUM USING IOT BASED SENSOR (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2026)
This study focuses on the development and application of a sensor-based system for monitoring key soil nutrients, namely Nitrogen (N), Phosphorus (P), and Potassium (K). An Arduino-based platform was employed to deploy sensors at multiple locations within the soil, enabling continuous real-time data acquisition. The collected data were systematically processed and analyzed to assess the spatial distribution and concentration of nutrients across the study area. The results were further interpreted through spatial visualization using the Inverse Distance Weighting (IDW) interpolation technique.The analysis revealed notable spatial variability in soil nutrient levels. Nitrogen concentrations were generally low in several areas, indicating a clear requirement for nitrogen fertilization. In contrast, phosphorus levels were predominantly high, suggesting that additional phosphorus application is unnecessary in most regions. Potassium levels showed localized deficiencies, highlighting the need for targeted potassium fertilization in specific zones.Overall, the findings provide valuable insights into the dynamics of soil nutrients in agricultural environments and demonstrate the effectiveness of modern technological approaches in supporting precision agriculture and improving nutrient management practices.